Examining the growth patterns of Brazilian cities - Daniel da Mata; Uwe Deichmann; J. Vernon Henderson; Somik V. Lall; Hyoung Gun Wang (Institute for Applied Economic Research (ipea), 2015)
The share of urban population in Brazil has increased from 58 to 80 percent between 1970 and 2000 and all net population growth over the next thirty years is predicted to be in cities. This paper explores population growth and its implications for economic dynamics and income generation among 123 urban agglomerations. Incomes are higher in larger agglomerations and in the South, but there is some indication of regional convergence with higher rates of income growth in poorer areas. In particular, agglomerations in the North and Central-West are growing faster than the more established urban centers in the South. Economic dynamics point to a process of increased diversification among larger cities, and greater specialization among medium sized agglomerations. In bigger centers there is a trend towards deconcentration towards the periphery. We close by providing a simple analysis of correlates of labor supply, as measured by population growth, and economic productivity, which is proxied by changes in per capita income.
Keywords: R11; O1; O47; 330